Planning of Gastronomic Tourism Destinations in Balikpapan City - Gozali, Gozali (E-Journal of Tourism; Volume 9 Number 2 (September 2022), 2022)
Planning the development of food-related tourist destinations often ignores the expectations of tourists themselves. This phenomenon almost occurs in various regions in Indonesia, especially in Balikpapan City. The purpose of this study is to analyze the planning of gastronomic tourism destinations from the tourists' perspective. This research was conducted using a descriptive survey method to determine the expectations of tourists visiting Manggar Beach in Balikpapan City regarding the gastronomic aspect. Data collection was carried out in April–June 2022 using an online questionnaire (google form), which was distributed to 117 respondents. The results of data collection were analyzed using SPSS 21.0 descriptively (frequency, arithmetic mean, and standard deviation). The scale of validity and reliability was measured. Research findings show that the gastronomy offered by culinary centers is less varied, most 76.9% of visitors have the habit of bringing raw food ingredients and cooking independently, 15.4% brought food and beverages from home, and 7.7% bought those available at culinary centers. Most of the visitors rated the satisfaction variable indicator in the unfavorable category, the lowest average value was Y2 (x? = 1.82, SD= 0.38) and the highest mean Y8 (x? = 2.50, SD = 0.76). Keywords: gastronomy; gastro tourism; destination planning; tourist expectations.